Design and Evaluation of PBL-STEM Based Electronic Worksheets Supported by PhET Virtual Physics Labs to Enhance Science Literacy - Pamungkas, Oky; Widowati, Asri; Kurniawan, Lilik; Agusta, Fauji (FKIP Universitas Lampung, 2024)
This study aims to produce PBL-STEM-based Student Worksheet Electronics assisted by PhET simulation on the topic of temperature and heat that is feasible and able to improve science literacy in a limited way by reviewing the results of N-Gain score analysis. The subjects in this study were students of class VII C SMP Muhammadiyah 3 Depok Sleman totaling 30 students, with 17 male and 13 female students. The research model used in this research is the 4-D (Four D) development model which consists of four stages, namely define, design, develop, and disseminate. The instruments in this study were interview guidelines, validation sheets, and students' pre-test and post-test questionnaires. Analysis of feasibility data was obtained through a validation questionnaire validated by three expert validators, while the improvement of science literacy was obtained through the results of limited trials. The data was obtained through the results of the pre-test and post-test given to students before the application of PBL-STEM-based Electronic Student Worksheets assisted by PhET simulation and after the application of PBL-STEM-based Electronic Student Worksheets assisted by PhET simulation. The validity results of this study obtained an average assessment score from the three expert validators of 93% with very valid criteria so that the PBL-STEM-based Electronic Student Worksheet aided by PhET simulation can be applied to science learning. The results of improving science literacy through limited testing of PBL-STEM-based Electronic Student Worksheets assisted by PhET simulation as an effect caused by the use of development products are creating a problem solution of 0.78, identifying scientific issues of 0.74, explaining scientific phenomena of 0.72 and using scientific evidance of 0.71. Overall, the increase obtained for each indicator is categorized as high, resulting in an average N-Gain value of 0.71 with high value criteria so that it can improve students' science literacy. Based on the results of the study, it is concluded that the development of PBL-STEM-based Electronic Student Worksheets assisted by PhET simulation is valid and can improve students' scientific literacy through limited tests with high N-Gain categories in each science literacy indicator. Keywords: elektronic student worksheet, problem based learning, STEM, science literacy.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1099-1112